Complex Brillouin Optical Time-Domain Analysis - Jian Fang; Miao Sun; Di Che; Myers, Matthew; Hongchun Bao; Prohasky, Colin; Shieh, William (Journal of lightwave technology, 2018)
We demonstrate a novel complex Brillouin optical time-domain analysis (BOTDA) approach for distributed fiber sensing that detects the complex Brillouin spectrum. Unlike other approaches, we utilize the complex nonlinear least-square regression technique to determine the Brillouin frequency shift (BFS) directly in the complex domain. The reduction of BFS uncertainty with our approach is shown through theoretical analysis and is validated by both simulations and experiments. Compared with either the gain-based or the phase-based BOTDA approaches, our complex BOTDA can improve the sensing accuracy by a factor of \sqrt {2} , which is equivalent to a 3 dB improvement in the power signal-to-noise ratio. Distributed temperature sensing is demonstrated over 40 km standard single-mode fiber. The experimental results agree well with the theoretical predictions of BFS uncertainty that confirms this considerable improvement.